Association of Household Economic Status and Birth Order with Stunting Among Children Aged 24-35 Months: Malawi MICS 2019–20 - Ngoma, Sibongire B; Adisasmita, Asri C.; Mahkota, Renti; Choirunisa, Septyana; Nyamukondiwa, Melisa (Jurnal Epidemiologi Kesehatan Indonesia, 2026)
Stunting remains a major public health concern in Malawi, with a national prevalence of 35.5% among children under five. However, evidence on the independent and combined effects of household economic status and birth order on stunting among Malawian children aged 24-35 months remains limited. This study aimed to examine the independent and combined association of household economic status and birth order with stunting among children aged 24-35 months in Malawi. A secondary data analysis of a cross-sectional 2019-20 Malawi Multiple Indicator Cluster Survey (MICS) was conducted, and the final sample comprised 2,764 children aged 24-35 months with complete data. Stunting was defined as a height-for-age Z-score below -2 SD. Weighted descriptive and bivariate analyses were performed, and potential confounding was assessed using stratified analyses and the change-in-estimate method (≥10% change in prevalence ratio). Multivariable models were specified a priori and included wealth index, birth order, child’s sex, and maternal education level. The weighted prevalence of stunting was 44.2% (95% CI: 41.3-47.1%). Household economic status, birth order, and their four-level combined variable were not independently associated with stunting after adjustment (p≥0.05). However, boys had a significantly higher prevalence ratio of stunting compared with girls (cPR= 1.23; 95% CI: 1.11-1.37; p Keywords: Stunting, Birth Order, Household Economic Status, Children Aged 24-35 Months, Cross-sectional Study, Malawi